Role of Participatory Forest Management (PFM) Institutions in the Management of Non-Timber Forest Products: A Roadmap from Kerala - George, Lijo P.; Alexander, George (Indian Forester, 2023)
Non-timber forest products (NTFP) provide both food and income to forest-dependent communities. The average daily revenue from NTFP gathering surpassed that of Kerala's average agricultural wage labour. The forest department, through its Participatory Forest Management institutions (VSS and EDC), provides necessary operational and technical assistance in the gathering and trading of NTFPs collected by native forest-dependent communities. The objective of the study is to analyze the strategies and projects employed by the forest department in the management of NTFPs in co-corporations with forest-dependent communities and PFM institutions. The NTFPs collected through PFM institutions are fresh and pure from the forests and are not been tampered with. â€œVanasreeâ€ is a unique venture established by the Kerala Forest and wildlife department under the State Forest Development Agency (SFDA) for the sale of Non-Timber Forest Produce collected by various forest-dependent communities. Virtual Go Down is a recently envisaged scheme of the Department of Forest and Wildlife to ensure uniformity in the management of NTFP under a single umbrella scheme. Forest Department plays a crucial role in supporting the livelihoods of forest-dependent communities by establishing and strengthening Participatory Forest Management (PFM) institutions. These institutions enable local communities to participate in sustainable forest management practices and utilize forest resources while ensuring their sustainable conservation.